THE EFFECTIVENESS OF FINE ART ACTIVITY ON STUDENTS’ SPEAKING ABILITY - Rohmah Adhawati; Eva Nurul Candra (STBA LIA - Jakarta, 2018)
The objective of this research was to get an empirical evidence of the effectiveness of using picture series toward students’ speaking ability in describing thing. The total sample of this study was 60 students. The method used in this research was a quantitative method. The design was a quasi-experimental study and the primary instrument of this research was a test. The result of the research showed a significant difference between the two classes’ in the final mean score of the post-test of the experimental class was 76.5, while the post-test means score of the controlled class was 73.1. The test of hypothesis showed that sig. 2 tailed (p) was 0.001 while alpha (α) was 0.005 (0.001 < 0.005). Therefore, it can be concluded that the use of Fine Art Activity can affect students’ speaking ability of seventh grade at SMP Negeri 13 South Tangerang.